Rysunek dziecka jako komunikat w diadzie komunikacji wizualnej dorosły- dziecko - Glinkowska, Dominika (Scripta Neophilologica Posnaniensia, 2022)
The work is an analysis of a visual communication in the adult-child communication field. The main aim of the study was to investigate the communicative potential of children’s drawing. In the first chapter issues of interpersonal communication, styles of speech, communication nishes and child’s artistic development were raised. Moreover, the role of the use of a non-verbal message in the communication process of an adult and a child was emphasized. The second chapter focuses on the issues of culture and visual communication, presents contemporary examples of the usage of high art in mass culture. The analysis of the role of a child’s drawing in the act of communication in the family, carried out in chapter three, showed that children are able to communicate perfectly with their parents not only through words, and parents (especially mothers) are aware of the potential of the content conveyed.